High occurrence of Bathyarchaeota (MCG) in the deep‐sea sediments of South China Sea quantified using newly designed PCR primers. Issue 4 (29th May 2017) - Yu, Tiantian; Liang, Qianyong; Niu, Mingyang; Wang, Fengping
Summary: The archaeal phylum Bathyarchaeota, which is composed of a large number of diverse lineages, is widespread and abundant in marine sediments. Environmental factors that control the distribution, abundance and evolution of this largely diversified archaeal phylum are currently unclear. In this study, a new pair of specific primers that target the major marine subgroups of bathyarchaeotal 16S rRNA genes was designed and evaluated to investigate the distribution and abundance of Bathyarchaeota in marine sediments. The abundance of Bathyarchaeota along two sediment cores from the deep‐sea sediments of South China Sea (SCS, each from the Dongsha and Shenhu area) was determined. A strong correlation was found between the bathyarchaeotal abundance and the content of total organic carbon (TOC), suggesting an important role of Bathyarchaeota in organic matter remineralisation in the sediments of SCS. Furthermore, diversity analysis revealed that subgroups Bathy‐2, Bathy‐8 and Bathy‐10 were dominant bathyarchaeotal members of the deep‐sea sediments in the SCS. Bathy‐8 was found predominantly within the reducing and deeper sediment layers, while Bathy‐10 occurred preferentially in the oxidizing and shallower sediment layers. Our study lays a foundation for the further understanding of the ecological functions and niche differentiation of the important but not well‐understood sedimentary archaeal group.